Performance Audit of Integrated Child Development Services (ICDS) in Bihar (2002-2007) - CAG of India (CAG of India, 2008)
The Integrated Child Development Services (ICDS) scheme, a central scheme was meant to deliver nutrition, education and health services, to children in the age group up to six years and enhance the capability of mothers through proper nutrition and health education. The implementation of the scheme in the State suffered from several deficiencies such as lack of planning, poor implementation of Supplementary Nutrition Programme, lack of infrastructure in Aganwadi centres (AWCs), failure to provide health check up and referral services. Main audit findings are summarised below: 1. There was no correlation between budget provision and number of functional Anganwadi centres. Budget preparation of the department was not realistic. 2. The GOI sanctioned 80302 AWCs against the requirement of 82833 but 60153 AWCs were operationalised as of July 2007. In test-checked projects, 97 per cent AWCs were running without toilet, drinking water facilities and 43 per cent were functioning in huts. 3. In test-checked CDPOs, rental payment of Rs 2.82 crore was transferred either in the bank accounts of sevikas or advanced to clerks instead of making direct payment to house owners. 4. Against target of 620 AWCs in 13 test-checked districts, only one AWC could be constructed up to August 2007 despite provision of Rs 8.29 crore (April- June 2005) to the District Magistrates. 5. No AWC provided nutritional support beyond 225 days as against requirement of 300 days during 2002-07. There was no evidence of distribution of take home ration. Nutri-candies provided to beneficiaries were found of sub standard quality. 6. Records relating to immunization, health cards, referral services, pre natal and post natal services, growth chart were not maintained at AWCs level. Medicine kits and Pre-school Education Kits were not supplied to AWCs as per ICDS norms. 7. Committees constituted to monitor the programme were non-functional and minutes of meetings and decisions taken were not available. Monitoring was almost negligible and 73 per cent AWCs visited were found closed during joint inspection.
For the Period 2002-03 to 2006-07